Wāqiʿ Taʿlīm al-Lughah al-ʿArabiyyah fī al-Maʿāhid wa al-Madāris bi-Indūnīsiyā - Ahmad Hidayatullah Zarkasyi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Arabic is one of the world's major languages and is widely taught in many countries, including Indonesia. Its introduction to Indonesia coincided with the arrival of Islam, leading the Muslim community to study it primarily as a means of understanding the Holy Qur’an. Today, Indonesia is witnessing significant progress in Arabic language education through the establishment of numerous schools and Islamic boarding schools that emphasize the teaching of Arabic alongside Islamic sciences. Although the methods of teaching Arabic vary across these educational institutions, they can generally be classified into two major approaches: the traditional method, which is commonly employed in traditional Islamic boarding schools and schools, and the modern method, which is adopted by contemporary educational institutions. One of the most prominent institutions implementing the modern approach is Darussalam Gontor Modern Islamic Boarding School. This article examines the various methods of Arabic language teaching in Indonesia, with particular attention to the modern approach practiced at Darussalam Gontor Modern Islamic Institution.